Brilliant graduate CV : how to get your first CV to the top of the pile - Bright, Jim (Pearson, 2014)
When you apply for your first job, your CV is compared to hundreds of others from graduates with similar academic credentials. You've only got the time it takes the employer to scan the pages to show how brilliant you are. How do you impress them when you don't know what employers are actually looking for? Brilliant CV tells you what they want and how to write it.